LEMBAGA PERKREDITAN DESA (VILLAGE CREDIT INSTITUSION) AS NON BANKING FINANCIAL INSTITUTION BASED CUSTOMARY LAW IN BALI - Suwitra, I Made; Arthanaya, I Wayan; Subawa, I Wayan; Sawitri Nandari, Ni Putu (Tadulako Law Review, 2020)
The study in this paper aims to show the strength of the Village Rural Institution owned by Desa Adat (costumory village) in Bali in the current globalization based on Awig-Awig (costumary law). This study is based on normative legal research methods and emperical law using satute approach, analytical, case, legal anthropology, and costumory law. The results of the study show that the presence of various financial institutions such as banking, finance, cooperatives have no significant effect on the existence of Lembaga Perkreditan Desa as a non-bank financial institution owned by Desa Adat. It is precisely the financial institutions established under state law are afraid of the existence of Rural Credit Institutions owned by Adat Village because of the strength of its legal alliance body and its awig-awig. So it can be concluded that the Village Rural Institution owned by Desa Adat in Bali can coexistence with various institutions and state law. Since the administration as a model of legal document used by Rural Credit Institution in credit distribution can imitate the model of banking administration in general with some adjustment to the local wisdom law for the welfare of the people of Desa Adat